Ruxolitinib Cream Has Dual Efficacy on Pruritus and Inflammation in Experimental Dermatitis - Scuron, Monika D.; Fay, Brittany L.; Connell, Andrew J.; Peel, Michael T.; Smith, Paul A. (Frontiers in Immunology, 2021)
The goal of this study was to elucidate the anti-pruritic and anti-inflammatory efficacy of ruxolitinib cream in experimentally-induced dermatitis. Atopic dermatitis (AD), the most common chronic relapsing inflammatory skin disease, significantly impairs patients’ quality of life, with pruritus being a common complaint. The sensation of itch results from the interplay between epidermal barrier dysfunction, upregulated immune signaling and the activation of the central nervous system. The Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway plays a central role in pro-inflammatory cytokine signaling in AD. Ruxolitinib cream is a potent and selective JAK1/2 inhibitor currently undergoing clinical evaluation in adults with mild-to-moderate AD (NCT03745638, NCT03538041 and NCT03745651). The efficacy of ruxolitinib cream was tested in murine models of acute and chronic dermatitis and was also characterized in an ex vivo human skin dermatitis model. Ruxolitinib cream was highly effective at ameliorating disease symptoms in multiple murine dermatitis models through downregulation of T helper (Th)2-driven inflammation, resulting in reduced skin thickening and decreased itch. Pathway analysis of mouse ear tissue and human skin explants underscored the role for ruxolitinib in ameliorating inflammation and reducing itch via modulation of the JAK-STAT pathway. Together, the data offer a strong rationale for the use of ruxolitinib cream as a potent therapeutic agent for the clinical management of atopic dermatitis.